ARCHITECTURAL UPCYCLING: BUILDINGS FROM WASTE & UNCONVENTIONAL MATERIALS - Mohamad Suhaimi, Edora; Mohammad Zin, Mohd Hafiz (Journal of Architecture, Planning and Construction Management, 2022)
Repurposing building materials has been practised since old civilisations, but recently, it has transcended to utilising not only building materials but to general waste items not typically used in construction. The practice is coined as architectural upcycling. Due to its unconventional nature, several drawbacks exist: the challenge of appropriating the item for its architectural purpose, the limitation on the type of buildings it can be applied to, and the scarcity of research that establishes a guide on architectural upcycling. This research aims to provide an insight on how to achieve the excellent practice of architectural upcycling through design considerations based on the type of buildings fit for this practice. The design considerations are outlined from reviewing previous studies, and the types of small-scale structures typically suitable are identified. Sixteen case studies are chosen from four small-scale typologies: community buildings, single residences, lodgings, and pavilions. Variables observed are the role of the material, functionality, modification, ability to be disassembled, and material expression. It is found that the buildings from the four typologies exhibit different approaches to addressing these considerations. The findings serve to guide designers in achieving successful upcycling practice based on the typologies studied.